PENERAPAN KAJIAN FEMINIS (Kajian Atas Karya Sachiko Murata, The Tao of Islam, A Sourcebook on Gender Relationship in Islamic Thought) - Muthoharoh, Lailatul; Oktora, Nency Dela; Putra, Muhammad Yusuf (Center of Gender Studies and Child of State Islamic Institute of Metro, 2020)
Application of Feminist Studies (Study of Sachiko Muratas Opus, The Tao of Islam, A Sourcebook on Gender Relationship in Islamic Thought). Allah creates human being in two genders that is man and woman, Allah has explained each rights and responsibilities in the holy book of Quran. Yet, other thoughts from several groups are emerged and said that the regulation of rights and responsibilities between men is not balanced, and put the woman as the lowest creature. Sachiko Murata has a different thought of man and woman position that argue the position of man and woman is not balance. He poured his thought on his book entitled The Tao of Islam. This book explains about his thought of gender relations in Islamic theology and cosmology.